THE USE OF DIGITAL TECHNOLOGIES IN THE PRACTICE OF ADAPTATION OF YOUNG PROFESSIONALS (Sociología y tecnociencia, 2024)
Adaptation technologies for young professionals used in the practice of institutions (enterprises) are included in the digitalization processes of personnel management, since staff resources need to be constantly improved based on innovative technologies. Adaptation is considered within the value based and professional approach as a personnel technology that ensures the improvement of the human capital of the enterprise. The article deals with the potential of digital technologies in the practice of adaptation of young professionals in the conditions of "labor shortage". The article addresses for the application of an institutional approach that allows estimation the effectiveness of the adaptation technology for young professionals used by educational institutions in Omsk (Russia). The structural-functional method determined the possibility of disclosing the adaptation content as an independent personnel technology included in the digitalization processes. The results of the study involve the identify the potential for digital adaptation of young professionals in educational institutions. The scientific value of the findings is in the classification of existing technologies for the adaptation of young professionals and the assessment of their potential in the context of the implemented personnel policy of an educational institution. The scientific novelty of the study consists in substantiating the potential of technologies for adapting employees used at enterprises in the real economy in educational institutions, which are traditionally limited in the choice of personnel policy by the executive body (founder).
Keywords: personnel policy; adaptation technology; digitalization; young professionals; educational institutions